2017
DOI: 10.1038/srep39863
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic and Anti-Inflammatory Effects of the Novel Semicarbazide-Sensitive Amine-Oxidase Inhibitor SzV-1287 in Chronic Arthritis Models of the Mouse

Abstract: Semicarbazide-sensitive amine oxidase (SSAO) catalyses oxidative deamination of primary amines. Since there is no data about its function in pain and arthritis mechanisms, we investigated the effects of our novel SSAO inhibitor SzV-1287 in chronic mouse models of joint inflammation. Effects of SzV-1287 (20 mg/kg i.p./day) were investigated in the K/BxN serum-transfer and complete Freund’s adjuvant (CFA)-evoked active immunization models compared to the reference SSAO inhibitor LJP-1207. Mechanonociception was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 59 publications
1
16
0
1
Order By: Relevance
“…The multiplicity of roles for PrAO in diverse processes has made it an important therapeutic target (O'Sullivan et al, ). Inhibitors of PrAO have been reported and its inhibition is known to have anti‐inflammatory effects and to positively influence vascular health, neurodegenerative disease progress and lung fibrosis, among other conditions (Horváth et al, , Jarnicki et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The multiplicity of roles for PrAO in diverse processes has made it an important therapeutic target (O'Sullivan et al, ). Inhibitors of PrAO have been reported and its inhibition is known to have anti‐inflammatory effects and to positively influence vascular health, neurodegenerative disease progress and lung fibrosis, among other conditions (Horváth et al, , Jarnicki et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Amendola et al previously reported that excessive accumulated polyamines in the intracellular or extracellular environment are oxidatively deaminated by amine oxidase producing toxic products [36]. In addition, vascular adhesion protein-1 (VAP-1), which is present at high levels in endothelial cells, decomposes polyamines to produce H 2 O 2 and acrolein, increasing oxidative stress [37]. In the present study, the topical administration of SPD signi cantly upregulated the expression of IL-6 and TNF-α in the wound site (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Following previous optimizations, all samples were tested undiluted in a blind fashion. Luminex 100 (Luminex Corporation, Austin, TX, USA) was used for the immunoassay and Luminex 100 IS software to analyze the bead median fluorescence intensity, as in our recent study ( 28 ). All the tests were run in duplicate.…”
Section: Methodsmentioning
confidence: 99%
“…As in previous studies by our group ( 28 , 29 ), total RNA was prepared using the TRI Reagent (Molecular Research Center, Inc., Cincinnati, OH, USA) and Direct-Zol™ RNA isolation kit (Zymo Research, Irvine, CA, USA) following the manufacturer’s instructions. Then, the samples were treated with DNase I (Zymo Research, Irvine, CA, USA) to remove contaminating genomic DNA and quantified with a NanoDrop ND-2000 spectrophotometer (NanoDrop Technologies, Wilmington, DE, USA).…”
Section: Methodsmentioning
confidence: 99%